Pemanfaatan Media Sosial Sebagai Media Komunikasi Massa Di Kalangan Pelajar - Ismatul Maula Hikmah; Rini Rusnawati; Nanda Silvia Br Galingging; Noerma Kurnia Fajarwati (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
Learning using text or conventional media makes it difficult for students to understand the material presented by the teaching staff. So now students use the YouTube application as a support in their learning activities. This research aims to find out more about the benefits of YouTube media for students and the use of YouTube social media as a place to share learning material. This research uses a descriptive method with a qualitative approach and this research uses data collection techniques including library research. The data used in this research is secondary data. The results of the research show that students who use YouTube as a mass communication medium make it very easy to find the information or knowledge they need and it is easier for students to understand the material contained in videos compared to material delivered directly by teachers or lecturers either online or face to face because of videos. on the YouTube application can be played back at any time to re-study the teaching material presented.